HALODOC APPLICATION USABILITY: A COMBINED SUS AND SEQ - Chara Aulia Urrohim; Andreas Rio Adriyanto (Adisam Publisher, 2025)
This research evaluates the usability of the Halodoc application for new users through an Interaction Design-based study. Quantitative methods, specifically the System Usability Scale (SUS) and the Single Ease Question (SEQ), were employed, supplemented by qualitative observation and interviews to diagnose User Interface (UI) and User Experience (UX) problems. Quantitative results revealed significant usability issues, demonstrated by an average SEQ score of 3.2 on a 1-7 scale. The average SUS score was 52.0, which categorizes the platform as